Effects of Environmental and Pathological Hypoxia on Male Fertility - Li, Zhibin; Wang, Sumin; Gong, Chunli; Hu, Yiyang; Liu, Jiao; Wang, Wei; Chen, Yang; Liao, Qiushi; He, Bing; Huang, Yu; Luo, Qiang; Zhao, Yongbing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Male infertility is a widespread health problem affecting approximately 6%-8% of the male population, and hypoxia may be a causative factor. In mammals, two types of hypoxia are known, including environmental and pathological hypoxia. Studies looking at the effects of hypoxia on male infertility have linked both types of hypoxia to poor sperm quality and pregnancy outcomes. Hypoxia damages testicular seminiferous tubule directly, leading to the disorder of seminiferous epithelium and shedding of spermatogenic cells. Hypoxia can also disrupt the balance between oxidative phosphorylation and glycolysis of spermatogenic cells, resulting in impaired self-renewal and differentiation of spermatogonia, and failure of meiosis. In addition, hypoxia disrupts the secretion of reproductive hormones, causing spermatogenic arrest and erectile dysfunction. The possible mechanisms involved in hypoxia on male reproductive toxicity mainly include excessive ROS mediated oxidative stress, HIF-1α mediated germ cell apoptosis and proliferation inhibition, systematic inflammation and epigenetic changes. In this review, we discuss the correlations between hypoxia and male infertility based on epidemiological, clinical and animal studies and enumerate the hypoxic factors causing male infertility in detail. Demonstration of the causal association between hypoxia and male infertility will provide more options for the treatment of male infertility